2007
DOI: 10.1073/pnas.0608773104
|View full text |Cite
|
Sign up to set email alerts
|

Modification of nuclear PML protein by SUMO-1 regulates Fas-induced apoptosis in rheumatoid arthritis synovial fibroblasts

Abstract: The small ubiquitin-like modifier (SUMO)-1 is an important posttranslational regulator of different signaling pathways and involved in the formation of promyelocytic leukemia (PML) protein nuclear bodies (NBs). Overexpression of SUMO-1 has been associated with alterations in apoptosis, but the underlying mechanisms and their relevance for human diseases are not clear. Here, we show that the increased expression of SUMO-1 in rheumatoid arthritis (RA) synovial fibroblasts (SFs) contributes to the resistance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
89
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 124 publications
(100 citation statements)
references
References 28 publications
9
89
1
1
Order By: Relevance
“…SUMO-1 can covalently modify a variety of proteins and modulates the downstream pathways of Fas signaling (5-7). Interestingly, it was shown recently that SUMO-1 is overexpressed in RA FLS when compared with osteoarthritic (OA) fibroblasts and contributes to the resistance of these cells to Fas-induced apoptosis (8). This study demonstrated that rather than interfering directly with the Fas molecule, sumoylation of the promyelocytic leukemia protein nuclear bodies and subsequent recruitment of the proapoptotic molecule Daxx into promyelocytic leukemia protein nuclear bodies constitute the mechanism by which SUMO-1 inhibits Fasinduced apoptosis in RA FLS.…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…SUMO-1 can covalently modify a variety of proteins and modulates the downstream pathways of Fas signaling (5-7). Interestingly, it was shown recently that SUMO-1 is overexpressed in RA FLS when compared with osteoarthritic (OA) fibroblasts and contributes to the resistance of these cells to Fas-induced apoptosis (8). This study demonstrated that rather than interfering directly with the Fas molecule, sumoylation of the promyelocytic leukemia protein nuclear bodies and subsequent recruitment of the proapoptotic molecule Daxx into promyelocytic leukemia protein nuclear bodies constitute the mechanism by which SUMO-1 inhibits Fasinduced apoptosis in RA FLS.…”
mentioning
confidence: 67%
“…FLS were grown in Dulbecco's modified Eagle's medium (DMEM; 10% fetal calf serum [FCS]) until passages 4-6, as previously described (8). Bone marrow-derived stromal cells were isolated by gradient centrifugation and plastic adherence.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations